Fiber Optic Pressure Measurements Open Up New Experimental Possibilities in Hydrogeology. Issue 1 (19th September 2021) - Leven, Carsten; Barrash, Warren
Abstract: Fiber‐optic (FO) technology is being used increasingly for measurement methods in a variety of environmental applications. However, FO pressure transducers are rarely used in hydrogeological applications. We review the current state of Fabry‐Pérot interferometry‐based FO pressure transducers, including their advantages and limitations, as another option for high‐resolution pressure‐ or head‐change measurements in conventional or advanced aquifer testing. Resolution and precision specifications of FO transducers meet or exceed commonly used non‐FO pressure transducers. Due to their design, FO transducers can be used in small‐diameter (inner diameter ≥1/4 inch) and continuous multichannel tubing (CMT), sampling points, multilevel packer systems, and Direct Push‐based in situ installations and testing. The small diameter of FO transducers provides logistical advantages—especially for tests with monitoring at many zones in a number of wells and/or CMTs (e.g., no reels, placement just below water level in access tubes vs. within isolated zones, reduced weight and volume, small footprint at single point of data acquisition). Principal limitations are small measurement drift that may become evident for tests longer than a few hours, and higher‐than‐average cost. We present field examples of FO transducer performance in short‐term tests with high consistency of acquired data and higher resolution (i.e., capturing significant hydrologic information) compared with commonly used non‐FO transducers. Given the above, including advantageous logistical features, FO transducers can open new experimental possibilities in areas of high‐resolution three‐dimensional (3D) heterogeneity (flow and transport, remediation, critical zones); 3D fracture networks and fundamental hydromechanical behavior; complex 3D flow and leak detection (mines, dams, repositories, geothermal systems).